A influência da Programação Fetal por Obesidade e Periodontite no Músculo Extensor Longo dos Dedos de Ratos Wistar - Cappellaro, Gabriella Lopes (2023)
the occurrence of stimuli or insults during intrauterine development, predisposing it to develop chronic diseases in adult life. Such insults may be maternal diseases, especially when they present a systemic inflammatory condition. However, the effects on skeletal muscle tissue in offspring are unclear. This study aimed to analyze whether FP caused by obesity and/or periodontitis (PD) causes morphological and morphometric changes in muscle fibers, connective tissue, and neuromuscular junctions (NMJs) in the extensor digitorum longus (EDL) muscle of the adult offspring of Wistar rats. In order to carry out the research, 20 pregnant Wistar rats were obtained, after the birth of the parental generation (P), the females were randomly distributed into two groups, at five days of life one group received the induction of obesity through injections of glutamate monosodium (MSG=30) the other group received hyperosmotic saline (n=30). At 70 days of age, 15 rats from each group received periodontitis induction through ligation. The P generation consisted of 60 female rats, divided into four groups according to the disease induction. At 77 days of age, five animals from each group were euthanized for disease verification. Subsequently, the crossing with control rats was carried out, constituting the F1 generation, composed of 28 male rats, forming four groups, namely: control (CTL-F1), periodontitis (PD-F1), MSG (MSG-F1) and MSG with periodontitis (MSG PD-F1). At 90 days of age, the animals received periodontitis induction and at 120 days they were euthanized and the EDL muscle was collected, stored, and processed for morphological and morphometric analyzes of muscle fibers by Hematoxylin-Eosin staining, quantification of connective tissue by the technique of Masson's Trichome, study of the NMJs by the Nonspecific Esterase reaction, and quantification of cholinesterase (ChE) enzyme activity. Statistical analysis was performed using the XLSTAT 2014.5.03 software, the results obtained were expressed as mean ± standard deviation of the mean, values with p<0.05 were considered significant. In the analysis of the macroscopic parameters of the offspring, the animals in the MSG PD-F1 group showed a reduction in body weight compared to the PD-F1 group. The MSG PD-F1 group showed a reduction in retroperitoneal and periepididymal fat and EDL muscle length compared to the MSG F1 and PD-F1 groups. However, nasoanal length measurements, Lee index and EDL muscle weight did not show statistical differences between the trained groups. In the morphology of the muscle fibers, fibers with a central nucleus and amorphous format were observed with dye differences in the MSG-F1, PD-F1, and MSG PD-F1 groups. In terms of morphometry, the PD-F1 group showed a reduction in fiber density and an increase in the capillary/fiber ratio compared to the CTL-F1 group. In connective tissue the MSG-F1 group had an increase compared to the CTL-F1 group, and the MSG PD-F1 group showed an increase compared to the PD-F1 group. NMJs and ChE enzyme activity did not differ significantly. The study revealed that the FP caused by obesity and PD, showed changes in the body parameters of the offspring, in muscle fibers and connective tissue, which may cause damage to muscle function.